Solvent free synthesis and characterization of few metal complexes of Schiff base derived from 2-Amino-5, 6-dimethyl benzimidazole & Syringaldehyde (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
A solvent free synthesis of bidentate Schiff base ligand was carried out by treating 2-Amino-5, 6-dimethyl benzimidazole with Syringaldehyde in 1:1 molar proportion in a scientific microwave oven. Excellent yield was obtained after purification. Few metal complexes of Schiff base were synthesized by using Mn(II), Fe(III), Co(II), Ni(II), Cu(II), Zn(II), Cd(II) and Ag(I) metal salts in microwave oven under solvent free condition. All metal complexes showed distinct color at the end of reaction and melting point of each complex preliminary confirmed the formation of product. A detailed characterization of both Schiff base & its representative metal complexes was carried out by several analytical & spectral techniques including elemental analysis, IR spectroscopy, 1HNMR spectroscopy, LCMS, UV spectroscopy and TGA. Spectroscopic analysis supports predicted structure of parent Schiff base ligand. Bioactivity of Schiff base & respective metal complexes was studied against Escherichia coli, Staphylococcus aureus & Salmonella typhi showing significant bioactivity of the metal complexes and Schiff base ligand.